IMPLEMENTATION OF INTERPROFESSIONAL COLLABORATIVE PRACTICE IN TYPE B TEACHING GENERAL HOSPITALS: A MIXED METHODS STUDY - Nurul Aida Fathya; Christantie Effendy; Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The concept of patient centered health services encourages interprofessional collaboration practice (IPCP), including teaching hospitals. IPCP in teaching hospitals expected to be implemented properly as a role model for students. Students in academic stage are expected to understand the concept of interprofessional education (IPE) and apply IPCP concept during clinical practice. This study aimed to determine the implementation of IPCP and various factors related to IPCP in teaching hospitals.Methods: This study used a mixed methods-sequential explanatory design with the subjects of healthcare professionals at RSUD R Syamsudin SH recruited using systematic random sampling. The research began with collecting quantitative data to measure the implementation of IPCP using the Indonesian version of the Assessment of Interprofessional Team Collaboration Scale-II (AITCS-II), continued with collecting qualitative data with in-depth interviews to explored IPCP and various factors associated with its implementation.Results: A total of 320 respondents filled out the AITCS-II questionnaire and 11 participants were interviewed deeply. More than 66% of respondents had a good collaboration in each domain; 73,8% of respondents had a good collaboration in IPCP; profession background significantly contributed IPCP (p <0.05). Qualitative analysis was carried out with a semantic theme and obtained 3 themes: not ideal IPCP implementation, perception of IPCP domains by healthcare professionals and barriers in implementing IPCP. Conclusion: The perception of IPCP that well implemented may resulted from improper understanding of IPCP. We still found barrier in implementing IPCP related to stereotypes, hierarchical culture, interprofessional communication and regulation.